2018
DOI: 10.1016/j.matdes.2018.05.005
|View full text |Cite
|
Sign up to set email alerts
|

3D-printing polymer-based permanent magnets

Abstract: Production of permanent magnets is a complex process that implies very specific machinery able to perform very specific actions. Even though this problem has been approached by extrusion-based three-dimensional printing techniques, the resulting parts either have not been fully characterized or present low-resolution outputs. In this study we use the stereolithography three-dimensional printing technique to address this problem and demonstrate that it is possible to develop high-resolution polymer-based perman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…Moreover, sedimentation is another major concern if micron-sized fillers are used [ 256 ]. There are a number of different studies where both materials and processes for vat-based printing of composite inks are studied in detail, refer to [ 255 , 256 , 269 , 270 , 271 ].…”
Section: Towards Magneto-active 4d Printingmentioning
confidence: 99%
“…Moreover, sedimentation is another major concern if micron-sized fillers are used [ 256 ]. There are a number of different studies where both materials and processes for vat-based printing of composite inks are studied in detail, refer to [ 255 , 256 , 269 , 270 , 271 ].…”
Section: Towards Magneto-active 4d Printingmentioning
confidence: 99%
“…It is reported that the viscosities of non-spherical Nd-Fe-B suspensions are generally higher than the viscosities of spherical Nd-Fe-B suspensions. [20][21][22] Therefore, the particle shape and size could not only affect the rheology of the binder but also the loading fraction in the polymer thereby altering the magnetic properties and thermal stability of the bonded magnets.…”
Section: Microstructurementioning
confidence: 99%
“…Direct ink writing (DIW) and fused filament fabrication (FFF) have been used to fabricate fast responding actuators, inks containing high loads of magnetic fillers and 2D planar structures that exploit folding and unfolding processes . Additionally, 3D printed permanent magnets were developed …”
Section: Introductionmentioning
confidence: 99%